Pengaruh Disiplin Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XI di SMA Negeri 1 Telaga Biru Kabupaten Gorontalo - Sudirman; Heti Setia Ningsih Rubama (Jurnal Pendidikan Ekonomi dan Bisnis, 2024)
This research aims to determine "The Effect of Learning Discipline on Students' Learning Outcomes in Economics Subject at Grade XI of Senior High School SMA Negeri 1 Telaga Biru, Gorontalo Regency". It employed a quantitative method, involving 85 students as the population and total sample; in addition, the instrument used in this study was a questionnaire. The results show that learning discipline does significantly affect students' leaming outcomes by arriving at the percentage of 75.2%. the rest 24,8% is influenced by other variables.